The effect of service quality and corporate image on staffs’ loyalty in UiTM Kelantan Branch / Nurul Qusna Mohd Zaki - Mohd Zaki, Nurul Qusna (2011)
This study investigated the staff loyalty among academic and non-academic staffs of University Technology MARA (UiTM) Kelantan Branch. Using quota sampling procedures, the 50 questionnaires were distributed to academic staff and then 50 questionnaires to non-academic staff in UiTM Kelantan Branch. All the questionnaires were returned back to us. Four variables, Corporate Image, Service Quality, Staff Satisfaction and Staff Loyalty were adopted for the study. The data was analyzed using SPSS 17.0 for descriptive analysis while Amos 17.0 was used for Structural Equation Modeling (SEM). The result showed that staff satisfaction has significant impact on staff loyalty. This is consistent with the findings of (Dick and Basu,1994)